PENGARUH GROWTH OPPORTUNITY, NET WORKING CAPITAL, CASH CONVERSION CYCLE DAN LEVERAGE TERHADAP CASH HOLDING PERUSAHAAN - Marfuah, Marfuah; Zulhilmi, Ardan (Optimum: Jurnal Ekonomi dan Pembangunan, 2015)
The purpose of this study was to examine the effect of growth opportunity, net working capital, cash conversion cycle and leverage on cash holding company. The population of this study are all companies listed on the Indonesia Stock Exchange from 2011 until 2013. By using purposive sampling method was selected sample of 276 over three years. Based on multiple regression analysis showed that the growth opportunity and net working capital have significant positive effect on cash holding company, while the cash conversion cycle and leverage have significant negative effect on cash holding company.